You'll never talk alone: What media narratives on European reforms reveal about a polity in the making - Emmanuel Mourlon-Druol; Henrik Müller; Giuseppe Porcaro; Tobias Schmidt (Bruegel, 2022)
This paper analyses the discourse since 2001 in three leading national business newspapers about reforms in the European Union: Handelsblatt (Germany), Il Sole (Italy) and Les Echos (France). We collected and organised a large dataset of articles published in these three newspapers. We used topic modelling to identify latent topics across articles. Based on this database, we then addressed four research questions and found: a relative degree of synchronisation of reform debates across the three countries; comparable reporting patterns, especially around the main crises; a greater degree of direction of the debate towards European issues over national issues in Germany than in France and Italy; and the tentative emergence of a shared narrative about crises. Finally, we highlight that bringing conflict and contestation back into European discussions may help stimulate wider interest in European matters.
Keywords: 330